RITUAL ISLAM KEJAWEN ANAK PUTU KI BONOKELING - Wita Widyandini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
Bonokeling society that lives in Pekuncen village, Jatilawang subdistrict,Banyumas regency, are the adherents of â€œIslam Blangkonâ€ orknown as â€œIslam Kejawenâ€. Ancestral figure who became a role modeland whom they ask for something is Bonokeling. As the adherents ofKejawen, Bonokeling people has many ritual beliefs, regularly scheduledand did not. This research aims to find the pattern of rituals procession ofBonokeling people and its influence on spatial settlement of the Bonokelingsociety.